Satisfacción de la atención de enfermería en usuarios del Centro de salud N°3 de la ciudad de Loja - Rivas Aguilar, Luis Alberto (2023)
User satisfaction is a quality indicator that health facilities apply more frequently to evaluate the effectiveness of the services offered. For this reason, the present study aimed to determine the level of satisfaction with nursing care among users of health center No. 3. It was a quantitative approach study, non-experimental design, descriptive scope and crosssectional study whose population consisted of 100 users from which a sample of 67 patients was obtained. For data collection, a simple random probabilistic sampling was used, using the survey technique and the questionnaire (CARE - Q) as an instrument, which has an internal validity of 0.88 to 0.97% according to Cronbach's Alpha coefficient and evaluates nursing care through 6 dimensions. The results obtained show that the users perceive a medium level of satisfaction, in relation to the predominant sociodemographic characteristics were the female gender with 68.7%, age between 20 and 64 years with 88.6%; the married marital status with 56.7%, the level of education was higher basic with 26.9%, they did not have insurance in 65.7% and the activity that they mostly perform are household chores with 47%, as for the dimensions the best qualified was: Maintains trust relationship with a high level of satisfaction of 40.3% followed by accessibility with 38.8%, while the lowest rated correspond to: comforts and anticipates with 19.45 and 22.4% respectively. Taking into account the results, emphasis should be placed on the specific care offered by the nursing professional, such as explaining the procedures to be performed, preparing a care plan in a timely manner and identifying real problems and strategies for improvement